The Effectiveness of Topical Plant Oils Against Pain in Knee Osteoarthritis Patient - Betty Luinta Saragih; Masfuri Masfuri; Dewi Gayatri (NurseLine Journal, 2022)
The prevalence of knee osteoarthritis (OA) patients will increase along with the escalation of life expectancy. Complementary and alternative therapies like topical plant oils have been used to reduce pain in several countries. However, the effectiveness of this topical plant oil is not yet known, especially in patients with knee OA in Indonesia. This study aims to assess the effectiveness of topical plant oils on pain for knee OA patients through literatures review. The literature search was conducted using 5 electronic databases, namely PubMed, ScienceDirect, Emerald Insight and Cochrane (Central). The search for literature that matches the topic of literature review using PICO, after that a review is carried out using the PRISMA method. On initial search found 412 journals, then filtered according to the inclusion criteria, which are full text, English, 2015-2020 publications, and Randomized Control Trial design. The journals be obtained were filtered again by the title and the abstract then read the full text. There were 7 selected journals that matched to the inclusion criteria and research purposes after a critical assessment using the Joanna Briggs Institute (JBI) checklist for Randomized Controlled Trials. Topical plant oils are effective in reducing joint pain without side effects. These positive findings can be applied in Indonesia. Combination with other non-pharmacological therapies is suggested in future studies to increase the effectiveness of topical plant oils for knee OA patients in reducing joint pain.